Reduced CCR5 expression among Uganda HIV controllers - Nyiro, Brian; Amanya, Sharon Bright; Bayiyana, Alice; Wasswa, Francis; Nabulime, Eva; Kayongo, Alex; Nankya, Immaculate; Mboowa, Gerald; Kateete, David Patrick; Sande, Obondo James (BioMed Central, 2023)
Abstract Background Several mechanisms including reduced CCR5 expression, protective HLA, viral restriction factors, broadly neutralizing antibodies, and more efficient T-cell responses, have been reported to account for HIV control among HIV controllers. However, no one mechanism universally accounts for HIV control among all controllers. In this study we determined whether reduced CCR5 expression accounts for HIV control among Ugandan HIV controllers. We determined CCR5 expression among Ugandan HIV controllers compared with treated HIV non-controllers through ex-vivo characterization of CD4 + T cells isolated from archived PBMCs collected from the two distinct groups. Results The percentage of CCR5 + CD4 + T cells was similar between HIV controllers and treated HIV non-controllers (ECs vs. NCs, P = 0.6010; VCs vs. NCs, P = 0.0702) but T cells from controllers had significantly reduced CCR5 expression on their cell surface (ECs vs. NCs, P = 0.0210; VCs vs. NCs, P = 0.0312). Furthermore, we identified rs1799987 SNP among a subset of HIV controllers, a mutation previously reported to reduce CCR5 expression. In stark contrast, we identified the rs41469351 SNP to be common among HIV non-controllers. This SNP has previously been shown to be associated with increased perinatal HIV transmission, vaginal shedding of HIV-infected cells and increased risk of death. Conclusion CCR5 has a non-redundant role in HIV control among Ugandan HIV controllers. HIV controllers maintain high CD4 + T cells despite being ART naïve partly because their CD4 + T cells have significantly reduced CCR5 densities.